STRES DAN CARA MENGATASINYA DALAM PERSPEKTIF PSIKOLOGI - Musradinur Musradinur (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2016)
Depression in daily life can give less flavor / discomfort, but it can also provide a sense of comfort. As an element that gives a sense of comfort it can be utilized, can be enjoyed, as well as the taste them, as well as a driving force to get ahead in life. As a factor that gives disires, it will cause a lot of complaints, in a state of acute anxiety in the form, in the form of chronic, physical or mental disorder, boredom, fatigue and eventually death. Management of depression is certainly pursuant nature. When he weighed on benefits in his life should be enjoyed. When he raises depression, in a state of acute, there are various alternatives to resolve it, either to the stress itself or its aftermath. In a state of chronic disorders that arise must be dealt with treatment. Here the role of the cooperation of various fields of medicine necessary if the interference is onganik. Psiklatri important role precisely in the face of such disorders. In the face of psychiatric disorders mural there are options on how to face up to the psychotherapy and pharmacotherapy.